Strategy Development for Puri Peliatan Heritage Tourism - Sucantra, Made Bayu; Budiasa, I Made; Nurjaya, I Wayan (Badan Riset dan Inovasi Daerah Provinsi Bali, 2021)
Purpose: This study aims to identify the strategy and program of Puri Peliatan (Peliatan Palace) as a heritage attraction in Peliatan Tourism Village, Ubud, Bali, Indonesia. Research methods: The data collection technique in this research is observation. Quotation is done from existing library materials, and other sources. Data analysis techniques used are descriptive-qualitative. Results and discussion: The main strategy planning of Puri Peliatan Ubud as an attraction of heritage tourism is by designing various programs. Puri Peliatan has a lot of tangible and intangible potential that can be developed as a tourist attraction, especially in heritage tourism. Implication: This study has a limited scope in identifying existing conditions of tourism in Puri Peliatan and Puri Peliatan planning as a heritage attraction so that a further study is needed.